Scenario of e-waste management: Navigating business prospects overcoming environmental challenges - Sarker, Debobrota Kumar; Shaha, Shompa Rani; Saha, Deepongkor; Saha, Mrinal Kanti; Saha, S. Mridul Kanti; Sarker, Bipul Kumar (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: The main objective of this study is to determine the scenario of e-waste management from a global and Bangladeshi perspective and navigate potential business prospects in the procedure of e-waste management minimizing health hazards. Research Methodology: The research was conducted by collecting data from reports and research papers from different international and national sources, interviews with 500 residents of Dhaka City, and five no. of recycling companies in Bangladesh. Upon descriptive analysis of the scenarios of global and Bangladeshi e-waste management, we tried to establish a relationship between proper e-waste management and business prospects. Results: The study found that home appliances and cell phones form the majority of e-waste. Informal recycling practices are responsible for high environmental and health risks. Moving towards a structured, formal recycling process can bring significant economic benefits in the form of employment opportunities and recovery of resources from e-waste. Conclusions: Effective e-waste management, supported by advanced technology and strong policy enforcement, is essential for protecting health and the environment while generating economic and employment opportunities. Limitations: The sample for the interview was taken from Dhaka City only. A larger population could make the study richer. Contribution: The study suggests setting up advanced recycling facilities and transforming entire e-waste management practices through internationally and cooperatively adopted sustainable measures. It emphasizes developing proactive policies and enhancing public awareness of proper e-waste management with a view to effectively facing the challenges and grabbing the business opportunities available from the e-waste management process. Novelty: This research has tried to bring out economic benefits and business opportunities from the process of e-waste management. It highlights that structured and sustainable e-waste management fosters economic growth, mitigates health hazards, and saves the environment.